167. A Bordetella pertussis Human Challenge Model Induces Immunizing Colonization in the Absence of Symptoms. (26th November 2018) - De Graaf, Hans; Ibrahim, Muktar; Hill, Alison; Gbesemete, Diane; Gorringe, Andrew; Diavatopoulos, Dimitri; Kester, Kent; Berbers, Guy; Faust, Saul; Read, Robert
Abstract: Background: Bordetella pertussis is one of the leading causes of vaccine preventable death and morbidity globally. Over the last 20 years, pertussis has resurged worldwide, even in territories with high immunization coverage. To improve vaccine strategies, a greater understanding of human B. pertussis infection and immunity is required. This study aims to develop a safe controlled human B. pertussis infection model and to define natural immune responses against wild-type B. pertussis in order to facilitate the development of bioassays and next-generation pertussis vaccines. Methods: In this first-in-human controlled infection model, healthy volunteers aged 18–45 years with an anti-pertussis toxin (PT) IgG level of <20 IU/mL were inoculated intranasally with B. pertussis strain B1917. Safety, colonization, and shedding were monitored over a 17-day inpatient period. Colonization was assessed by culture and qPCR of nasal washes and nasopharyngeal swabs. Azithromycin eradication therapy was commenced on day 14. The dose of inoculum was escalated to optimize colonization rate, expressed as the percentage of volunteers colonized at any sampling point between day 3 and 14. The immunological response is being assessed at various time points over 1 year. Results: 24 volunteers were challenged in groups of 4–5. The dose was gradually escalated from 10 3 colony forming units (cfu) to 10 5 cfu. Colonization rate ranged from 0% (dose 10 3 cfu) to 80% (10 5 cfu). Amongst this initial cohort, no significant safety concerns or symptoms attributed to B. pertussis disease were reported. Eradication was achieved by 48 hours in 100% of colonized volunteers. At least 4-fold rise in anti-PT IgG by day 28 in comparison to baseline was observed in 5 out of 8 volunteers who had >1, 000 cfu/mL viable B. pertussis in the nasal wash and in one volunteer without detectable colonization. Nasal wash cultures were more sensitive in detecting colonization than nasopharyngeal swab cultures. No shedding of B. pertussis was detected in systematically collected environmental samples. Conclusion: This is the first study to demonstrate safe deliberate induction of B. pertussis colonization. It shows that asymptomatic B. pertussis colonization occurs and causes a systemic immune response. The model that we have developed will be a valuable tool to further investigate B. pertussis colonization and vaccine development. Disclosures: K. Kester, Sanofi: Employee, Salary. S. Faust, Pfizer, Merck, Sanofi, AstraZeneca/Medimmune: Scientific Advisor, all honoraria paid to institution with no personal payments of any kind.